Association Between Diastolic Blood Pressure During Pediatric In-Hospital Cardiopulmonary Resuscitation and Survival. Issue 17 (24th April 2018) - Berg, Robert A.; Sutton, Robert M.; Reeder, Ron W.; Berger, John T.; Newth, Christopher J.; Carcillo, Joseph A.; McQuillen, Patrick S.; Meert, Kathleen L.; Yates, Andrew R.; Harrison, Rick E.; Moler, Frank W.; Pollack, Murray M.; et al.
Abstract : Background: On the basis of laboratory cardiopulmonary resuscitation (CPR) investigations and limited adult data demonstrating that survival depends on attaining adequate arterial diastolic blood pressure (DBP) during CPR, the American Heart Association recommends using blood pressure to guide pediatric CPR. However, evidence-based blood pressure targets during pediatric CPR remain an important knowledge gap for CPR guidelines. Methods: All children ≥37 weeks' gestation and <19 years old in Collaborative Pediatric Critical Care Research Network intensive care units with chest compressions for ≥1 minute and invasive arterial blood pressure monitoring before and during CPR between July 1, 2013, and June 31, 2016, were included. Mean DBP during CPR and Utstein-style standardized cardiac arrest data were collected. The hypothesis was that DBP ≥25 mm Hg during CPR in infants and ≥30 mm Hg in children ≥1 year old would be associated with survival. Primary outcome was survival to hospital discharge. Secondary outcome was survival to hospital discharge with favorable neurological outcome, defined as Pediatric Cerebral Performance Categories 1 to 3 or no worse than prearrest baseline. Multivariable Poisson regression models with robust error estimates were used to estimate the relative risk of outcomes. Results: Blinded investigators analyzed blood pressure waveforms during CPR from 164 children, including 60% <1 year old, 60% with congenital heart disease, and 54% after cardiac surgery. The immediate cause of arrest was hypotension in 67%, respiratory decompensation in 44%, and arrhythmia in 19%. Median duration of CPR was 8 minutes (quartiles, 3 and 27 minutes). Ninety percent survived the event, 68% with return of spontaneous circulation and 22% by extracorporeal life support. Forty-seven percent survived to hospital discharge, and 43% survived to discharge with favorable neurological outcome. Maintaining mean DBP ≥25 mm Hg in infants and ≥30 mm Hg in children ≥1 year old occurred in 101 of 164 children (62%) and was associated with survival (adjusted relative risk, 1.7; 95% confidence interval, 1.2–2.6; P =0.007) and survival with favorable neurological outcome (adjusted relative risk, 1.6; 95% confidence interval, 1.1–2.5; P =0.02). Conclusions: These data demonstrate that mean DBP ≥25 mm Hg during CPR in infants and ≥30 mm Hg in children ≥1 year old was associated with greater likelihood of survival to hospital discharge and survival with favorable neurological outcome. Abstract : Supplemental Digital Content is available in the text.